(untitled) (Journal of Sciences & Technology, 2020)
Knowing that the rehabilitation practice in Algeria is not codified yet, the principal aim of this paper is to evaluate seismic performance of retrofitted reinforced concrete buildings by CFRP wrapping using a Pushover analysis to estimate the structural capacity in both strength and ductility. A nonlinear analysis is conducted on a series of low-rise buildings with poor concrete strength of their vertical components where the CFRP wrapping is adopted as a rehabilitation solution. An explanation of the simulation work before and after the retrofitting operation is given through the modeling approach of the nonlinear sectional behavior based on a combination of confining effects, helping in Moment-Curvature analysis and user defined plastic hinges modeling. Finally, seismic performance enhancement is evaluated in local and global behavior considering several structural criteria.